Trophodynamics and reproductive biology of Otolithoides biauritus (Cantor) landed by trawlers at Vanakbara, Diu along the west coast of India - Ghosh, Shubhadeep; Mohanraj, G; Asokan, P K; Dhokia, H K; Zala, M S; Bhint, H M (Indian Journal of Fisheries, 2016)
The trophodynamics and reproductive biology of koth Otolithoides biauritus caught by trawlers at Vanakbara, Diu wasstudied for the period from September 2005 to May 2008. The length-weight relationship showed that growth was allometricand there was no significant difference between the sexes. The overall sex ratio was 1:1.09 with mature females occurringthroughout the year. The peak breeding season was in the monsoon season from May to August as evidenced by maturitystages, gonado-somatic index and the size progression of yolked ova. The length at first maturity of the female was110.15 cm. The absolute fecundity ranged from 1,82,020 to 1,941,400. The mature ovaries of O. biauritus contained twobatches of mature ova measuring from 0.75 to 0.79 mm and 0.65 to 0.69 mm in diameter. O. biauritus was found to feed moreintensely during the post-monsoon months. The most important food item was Acetes spp. followed by finfishes. Fishespossessing empty stomachs were frequently encountered in the commercial catch. Young ones of O. biauritus fed moreabundantly than adults with penaeid prawns dominating the gut contents while adults preferred finfishes as their diet.